2006
DOI: 10.1038/sj.bjc.6603490
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of imbalanced genes in prostate carcinoma using tissue microarrays

Abstract: To identify candidate genes relevant for prostate tumour prognosis and progression, we performed an exhaustive gene search in seven previously described genomic-profiling studies of 161 prostate tumours, and four expression profiling studies of 61 tumours. From the resulting list of candidate genes, six were selected for protein-expression analysis based on the availability of antibodies applicable to paraffinised tissue: fatty acid synthase (FASN), MYC, b-adrenergic receptor kinase 1 (BARK1, GRK2) the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 30 publications
2
57
0
Order By: Relevance
“…The correlation between reduced expression of the NM23-H1 gene and a higher metastatic potential and worse prognosis has been shown in carcinomas of the breast, 20,21 liver, 22 lung 23 and prostate. 24 On the contrary, the opposite trend has been reported in thyroid carcinomas, 25 neuroblastoma, 26 and head and neck carcinomas. 27 Obviously, the NM23-H1 protein has a different and possibly variable role in tumors of different origins.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between reduced expression of the NM23-H1 gene and a higher metastatic potential and worse prognosis has been shown in carcinomas of the breast, 20,21 liver, 22 lung 23 and prostate. 24 On the contrary, the opposite trend has been reported in thyroid carcinomas, 25 neuroblastoma, 26 and head and neck carcinomas. 27 Obviously, the NM23-H1 protein has a different and possibly variable role in tumors of different origins.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that expression of βARK1, which desensitizes ADRB2, is lost in prostate tumors with high Gleason scores. This may lead to prolonged activation of adrenaline/ADRB2/PKA/BAD signaling (52).…”
Section: Figurementioning
confidence: 99%
“…Intricate interplay of dephosphorylation and kinase activity governs the normal process of cell cycle. Genetic alterations in the catalytic and regulatory subunits of these protein phosphatases have been reported in various human cancers including oral squamous cell carcinoma and prostate cancer (41,42). In an extensive study of genetic alterations compiled using oligonucleotide-based array, comparative genomic hybridization showed that 11q13.4 is differentially deleted specifically in primary glioma as opposed to secondary GBM and has been classified as high-priority primary GBM subtype-unique minimal common regions.…”
Section: Discussionmentioning
confidence: 99%